Urgensi Perubahan Kurikulum K13 dengan Kurikulum Merdeka Serta Pengaruhnya di SDN 064037 Medan Tembung - Aufa Aufa; Ardina Khoirunnisa; Buti Sarma Sitompul; Iga Nailah Aulia Br lubis; Nur Adila; Wafi Harahap (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Education is a very important factor for the development of a country. Education helps develop and improve skills and improves the quality of life and human dignity. To date, changes have been made to the curriculum. The curriculum is considered a plan developed to facilitate the teaching and learning process which is the responsibility of the school or educational institution and its teaching staff. (Yulia, 2023). Education in Indonesia has undergone curriculum changes 11 times. Starting from after independence until the latest in 2021-2022. This research aims to compare the implementation of the 2013 Curriculum and the Merdeka Curriculum at State Elementary School 064037 and understand the differences between the two in improving the quality of education. The method used is qualitative research with a content analysis and narrative analysis approach. In-depth content analysis is carried out on written and printed information from mass media to identify message characteristics objectively and systematically. Data was collected through interviews and reviewing controversial mass media news. The research results show that the Merdeka Curriculum, which has only been implemented in grades 1 and 4, gives students greater freedom in the use of knowledge, both inside and outside school, and encourages teacher and student creativity. In contrast, the 2013 Curriculum balances soft skills and hard skills in an integrative manner but still places educators as the main assessors of student abilities. Observations show that the Merdeka Curriculum encourages students to play an active role in learning, with educators acting as facilitators. This change in curriculum leads to a more student-centric approach, where students receive active feedback regarding their self-evaluation. These findings confirm that the Merdeka Curriculum promotes more independent and participatory learning compared to the 2013 Curriculum.